2018
DOI: 10.1371/journal.pone.0206277
|View full text |Cite
|
Sign up to set email alerts
|

Intracorporeal versus extracorporeal anastomosis for minimally invasive right colectomy: A multi-center propensity score-matched comparison of outcomes

Abstract: BackgroundThe primary objective of this study was to retrospectively compare short-term outcomes of intracorporeal versus extracorporeal anastomosis for minimally invasive laparoscopic and robotic-assisted right colectomies for benign and malignant disease. Recent studies suggest potential short-term outcomes advantages for the intracorporeal anastomosis technique.MethodsThis is a multicenter retrospective propensity score-matched comparison of intracorporeal and extracorporeal anastomosis techniques for lapar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
64
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 37 publications
0
64
0
1
Order By: Relevance
“…So far, the only clinical evidence is offered by retrospective low powered studies that indicate faster bowel movements, earlier re-feeding and shorter postoperative hospital stay after LRH with ICA. Prospective comparative multicenter studies comparing perioperative outcomes of ECA versus ICA are still missing [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27].…”
mentioning
confidence: 99%
“…So far, the only clinical evidence is offered by retrospective low powered studies that indicate faster bowel movements, earlier re-feeding and shorter postoperative hospital stay after LRH with ICA. Prospective comparative multicenter studies comparing perioperative outcomes of ECA versus ICA are still missing [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27].…”
mentioning
confidence: 99%
“…In this review, only one study documented a significant increase in anastomotic leaks in patients undergoing laparoscopic ECA as opposed to robotic ICA . In addition, a propensity score matching study of robotic and laparoscopic formed anastomosis reported that minimally invasive ICA was associated with significantly shorter hospital stay and lower complication rates after discharge to 30 days than the ECA group . Similarly, this systematic review reports significantly lower hospital LOS in patients following RRH.…”
Section: Discussionmentioning
confidence: 74%
“…This is mainly attributed to the need for hand-sewing and knotting inside the abdominal cavity, and many surgeons required further training to perform intracorporeal sutures e ciently. The longer surgical time required to perform IA is also mentioned by several studies [5,8,11,12]; however, we predict that this may shorten with increased surgical experience and the establishment of a standard approach. Given that EA requires grasping of the colon and ileum for subsequent anastomosis, a trans-umbilical incision is usually chosen and the length of the wound is inevitably longer; however, using IA, any incision site can be selected for specimen retraction and the length of the wound can be shorter for grasping one longer specimen.…”
Section: Long-term Postoperative Outcomesmentioning
confidence: 72%